Spatial analysis and social spaces Interdisciplinary approaches to the interpretation of prehistoric and historic built environments - Lieberwirth, Undine; Paliou, Eleftheria; Polla, Silvia (De Gruyter, 2014)
In recent years a range of formal methods of spatial analysis have been developed for the study of human engagement, experience and socialisation within the built environment. This volume brings together contributions from a number of specialists in archaeology, social theory, architecture, and urban planning, who explore the theoretical and methodological frameworks associated with the application of established and novel spatial analysis methods in prehistoric and historic built environments. The authors discuss the relationship between space and social life from different perspectives and provide many illuminating examples of computer-based spatial analysis methods in archaeology
Keywords: Analyse spatiale (Statistique) en archéologie; Archéologie; Architecture antique; Archaeology; Architecture, Ancient; Spatial analysis (Statistics) in archaeology; Archaeology -- Methodology -- Congresses; Architecture, Ancient -- Congresses; Spatial analysis (Statistics) in archaeology -- Congresses; Vor- und Frühgeschichte; Sozialraum; Dreidimensionale Computergrafik; Städtebau; Räumliche Statistik; Stadtplanung; Mittelmeerraum; Electronic books; Conference papers and proceedings; Konferenzschrift